PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN (SIM), KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KOTA BIMA - Sulastri Dewi; Hermanto Hermanto; Lina Warlina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to analyze the influence of management information systems, communication and work motivation on the performance of employees of the Bima City Social Service. This research is a causal research (cause-effect), meaning that this research is a quantitative study to analyze the causal effect between Management Information Systems, Communication and Motivation on Employee Performance at the Bima City Social Service. The sample of this study were 71 civil servants and non-civil servants who served at the Bima City Social Service. The research instrument is a questionnaire that uses a Likert scale. Then the data were analyzed using multiple linear regression analysis. The results of the descriptive analysis explain that the implementation of the Management Information System (MIS) is classified as good, which means that it supports the implementation of tasks, as well as regarding communication that the average respondent has a good communication pattern, not to mention the average work motivation is high and employee performance is high. as expected. The results of the regression analysis show that (1) the Management Information System has a positive and significant influence on employee performance; (2) Communication has a positive and significant influence on employee performance; (3) Motivation has a positive and significant effect on employee performance; and (4) Management information system (MIS), communication and work motivation simultaneously have a significant influence on the performance of the Bima City Social Service employee. Therefore, to improve employee performance, it is necessary to jointly improve the SIM variable, good communication, and increase work motivation.